KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH PADA DINAS PENDAPATAN DAERAH KABUPATEN BOGOR - Dede Suleman (Universitas Bina Sarana Informatika, 2017)
local government, taxes levied under national regulations, but tariff revenues are made by local governments Taxes levied and administered by the central government, but levies are distributed to local governments. local taxes included; hotel taxes, restaurant taxes, entertainment taxes, street lighting taxes, advertisement taxes, property and urban taxes, land and building rights, swiftlet nest taxes.Object of restaurant tax is service provided with payment, Service provided restaurant referred to include service of sale of food and / or beverage consumed by buyer, either consumed in place of service or elsewhere. Which is not the object of restaurant tax is catering service or catering and services provided by restaurants or restaurants whose sales value does not exceed ten million rupiah per month. The subject of restaurant tax is an individual or entity that makes payment to restaurants / restaurants, cafes, bars and the like, while taxpayers are individuals or entities that run the restaurant. restaurant tax revenues increased annually to contribute to local revenues, Bogor Regency revenue offices, restaurant tax contribution in 2014 was 1.06%, 1.17% in 2015 and 2016 was 1.48%. each year shows an increase and targets and realization, in 2014 its achievement target of 103.56%, in 2015 its target achievement of 110.12%, 2015 its achievement target of 102.35%. . The restaurant tax has already been set at a rate of ten per cent of the amount of payment the restaurant receives